Association between serum Vitamin D levels and sperm DNA fragmentation index in varicocele patients: a retrospective cohort study - Tianhong Cai; Rong Zhang; Kai Chen; Jianfeng He; Tenghui Zhan (Reproductive Biology and Endocrinology)
Abstract Objective While varicocele is a major cause of male infertility, the role of vitamin D in sperm DNA integrity remains unclear. This study aimed to investigate the association between serum vitamin D levels and sperm DNA fragmentation index (DFI) in varicocele patients. Methods This retrospective cohort study conducted at Fujian Maternity and Child Health Hospital included 355 varicocele patients aged 18–45 years (June 2021-June 2024). The primary exposure was serum 25-hydroxyvitamin D level, and the primary outcome was DFI. Multiple linear regression models were used to analyze the association between vitamin D and DFI, adjusting for age, BMI, smoking, alcohol consumption, and other confounders. Results A significant inverse association was found between vitamin D levels and DFI (β = -0.24, 95% CI: -0.28 to -0.19, P < 0.0001). Piecewise linear regression identified a threshold at 25.9 nmol/L, below which the inverse association was more pronounced (β = -1.0, 95% CI: -1.2 to -0.8, P < 0.001). Conclusion Serum vitamin D levels have been demonstrated to be significantly associated with the rate of sperm DNA fragmentation index in patients with varicocele, particularly at levels below 25.9 nmol/l.